Immunobiology of hepatitis B virus infection - Isogawa, Masanori; Tanaka, Yasuhito (Hepatology research, 2015)
The adaptive immune response, particularly the virus‐specific CD8+ T‐cell response, is largely responsible for viral clearance and disease pathogenesis during hepatitis B virus (HBV) infection. The HBV‐specific CD8+ T‐cell response is vigorous, polyclonal and multispecific in acutely infected patients who successfully clear the virus and relatively weak and narrowly focused in chronically infected patients. The immunological basis for this dichotomy is unclear. A recent study using HBV transgenic mice and HBV‐specific T‐cell receptor transgenic mice suggests that intrahepatic antigen presentation by HBV positive hepatocytes suppresses HBV‐specific CD8+ T‐cell responses through a co‐inhibitory molecule, programmed cell death 1 (PD‐1). In contrast, antigen presentation by activated professional antigen‐presenting cells induces functional differentiation of HBV‐specific CD8+ T cells. These findings suggest that the outcome of T‐cell priming is largely dependent on the nature of antigen‐presenting cells. Another study suggests that the timing of HBV‐specific CD4+ T‐cell priming regulates the magnitude of the HBV‐specific CD8+ T‐cell response. Other factors that could regulate HBV‐specific cellular immune responses are high viral loads, mutational epitope inactivation, T‐cell receptor antagonism and infection of immunologically privileged tissues. However, these pathways become apparent only in the setting of an ineffective cellular immune response, which is therefore the fundamental underlying cause. Understanding the cellular and molecular mechanisms by which HBV evades host immune responses will eventually help develop new immunotherapeutic strategies designed to terminate chronic HBV infection.